Kenakalan pada remaja madya: Bagimana peran keberfungsian keluarga? - Rivanda Aulia Rachmah; IGAA Noviekayati; Aliffia Ananta (INNER: Journal of Psychological Research, 2023)
This study aims to determine the relationship between family functioning and juvenile delinquency that occurs in middle adolescents at one of the X State Junior High Schools in Surabaya City. Participants in this study were adolescents with an age range of 13-16 years with a sample of 89 students consisting of 43 grade 7 students and 46 grade 8 students. The sampling technique used in this study is the quota sampling technique. Data collection in this study used the family functioning scale and juvenile delinquency scale and was analyzed using the Pearson product-moment correlation test. Based on the results of data analysis, it can be concluded that the higher the level of family functioning, the lower the juvenile delinquency, and vice versa. Keywords: Family functioning, juvenile delinquency, middle juveniles.